Programa Educativo de inteligencia emocional para disminuir niveles de agresividad de los alumnos de Segundo Grado de Secundaria de la I.E. Leoncio Prado Gutiérrez del Distrito del Provenir - 2015 - Reyes Sagástegui, Elci Violeta (2018)
ABSTRACT The most important points of the research carried out whose main objective was to determine to what extent the application of the educational program of Emotional Intelligence decreases the level of aggression in the 2nd grade students of secondary education of the Educational Institution "Leoncio Prado Gutiérrez "Of the District the Porvenir- 2015. The quasi-experimental design of 2 groups with pre- and post-test application was used, for which a sample of 60 second-grade Secondary Education students from the I.E. N ° 80627 Leoncio Prado Gutiérrez of the district of Porvenir divided into 2 groups (Control section "B" and experimental section "C"). The experimental proposal consisted of an interactive and experiential emotional intelligence educational program, in which didactic strategies were implemented to favor empathy, control of emotions and social skills, in a period of 4 months. After applying the pre and posttest of aggressiveness, it was determined that the application of the Emotional Intelligence educational program decreased the level of aggressiveness in the experimental group from 76% to 12% in the high level, in addition the average aggressiveness decreased from 39.5 to 15.4, while in the control group a high level of aggression was maintained (64%). Likewise, the test of the difference hypothesis of means allowed to establish that the mean of the experimental group was significantly greater than that of the control group, since the p value was p = 0.002.